Polythiophene-Chitosan Magnetic Nanocomposite as a Highly Efficient Medium for Isolation of Fluoxetine from Aqueous and Biological Samples - Feizbakhsh, Alireza (J Anal Methods Chem, 2016)
Polythiophene/chitosan magnetic nanocomposite as an adsorbent of magnetic solid phase extraction was proposed for the isolation of fluoxetine in aqueous and biological samples prior to fluorescence detection at 246 nm. The synthesized nanoparticles, chitosan and polythiophene magnetic nanocomposite, were characterized by scanning electron microscopy, FT-IR, TGA, and EDAX. The separation of the target analyte from the aqueous solution containing the fluoxetine and polythiophene/chitosan magnetic nanocomposite was simply achieved by applying external magnetic field. The main factors affecting the extraction efficiency including desorption conditions, extraction time, ionic strength, and sample solution pH were optimized. The optimum extraction conditions were obtained as 10 min for extraction time, 25 mg for sorbent amount, 50 mL for initial sample volume, methanol as desorption solvent, 1.5 mL for desorption solvent volume, 3 min for desorption time, and being without salt addition. Under the optimum conditions, good linearity was obtained within the range of 15–1000 μg L(−1) for fluoxetine, with correlation coefficients 0.9994. Furthermore, the method was successfully applied to the determination of fluoxetine in urine and human blood plasma samples. Compared with other methods, the current method is characterized with highly easy, fast separation and low detection limits.